2022
DOI: 10.51847/ikq2hu7kcp
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Insects on Four Cashew Nut Varieties Inflorescences “Anacardium occidentale L.” in Niofoin “Côte d’Ivoire”

Abstract: Cashew nut represents the third most exported agricultural product of Côte d'Ivoire. However, the yield production of cashew is still low likely due to many factors including under-pollination. This study aims to identify the insects visiting cashew tree inflorescences at Niofoin in northern Côte d'Ivoire. Observations were made in a cashew orchard measuring two hectares. Insects visiting the inflorescences were captured and identified. A total of four cashew nut varieties (Yellow Benin, Henry, Costa Rica, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
4
1
Order By: Relevance
“…This study also corroborates with the study by Park et al [10] who reported that despite the change in external temperature, the internal temperature was maintained above 31°C. Contrastingly, the hive temperature values was slightly higher than that of Tuo et al [13] and Floris et al (2020) who reported that bee's activity evolves within adequate temperature range of 34°C and 35°C. [12] who compared the effect of entrances on hive microclimate.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…This study also corroborates with the study by Park et al [10] who reported that despite the change in external temperature, the internal temperature was maintained above 31°C. Contrastingly, the hive temperature values was slightly higher than that of Tuo et al [13] and Floris et al (2020) who reported that bee's activity evolves within adequate temperature range of 34°C and 35°C. [12] who compared the effect of entrances on hive microclimate.…”
Section: Discussioncontrasting
confidence: 58%
“…For instance, the modifications of hive entrances was previously reported to significantly affect the temperature and relative humidity variations of hives [4,12]. Tuo et al [13] used pan traps (UV-brilliant blue, yellow and white) to analyse the impact of different agroecosystems on bee activity in hives and found that bee activity evolves with temperature (34°C and 35°C) up to a certain point and inversely with relative humidity (56% and 65%). Furthermore, pollination in natural and agricultural systems is affected by bees' responses to changing environmental temperatures, with rising average temperatures resulting to pollinator population declines [14].…”
Section: Introductionmentioning
confidence: 99%
“…The specific richness in protected areas is higher than in anthropised areas (Bondé et al, 2013). Tuo et al (2019) reported that honey bees can adapt well to anthropised areas. Indeed crops ( Gossypium hirsutum L., Sesamum indicum L., Zea mays L.) and some cultivated woody plants ( Anacardium occidental L.; Eucalyptus camaldulensis Dehnh.)…”
Section: Discussionmentioning
confidence: 99%
“…Foraging activity increases with temperature until an optimum temperature is reached below or above which the opposite effect is observed. Tuo et al (2019) observed maximum bee activity between 11:00 AM and 02:00 PM when the temperature ranged between 34°C and 35°C. In Burkina Faso, Schweitzer et al (2013) indicated that the optimal foraging temperature of the local honey bees was between 25°C and 35°C and the periods of high temperatures are linked to the periods when the local honey bees are most active.…”
Section: Discussionmentioning
confidence: 99%
“…The Apini bee tribe, whose species is Apis mellifera, is the best known and responsible for honey production (Tuo et al, 2019) in Côte d'Ivoire, as well as by-products. In addition, honey from species of the Hypotrigona/Liotrigona genus (small bees) is consumed by local populations (Soro et al, 2020).…”
Section: Bees Studiedmentioning
confidence: 99%